The Analysis of Translation Quality of Indonesian Subtitle in the Forrest Gump Film - Eryanto, Mada Oktavian; Baharuddin, Baharuddin; Isnaini, Muh.; Putera, Lalu Jaswadi (Jurnal Ilmiah Profesi Pendidikan, 2024)
Film has beneficial effects for English learners especially audience from other country, therefore it is necessary to have high-quality translation in form of subtitle. This study aimed to find out the translation quality of Indonesia subtitle in the “Forrest Gump” film. The methods to assess this translation quality by applying Juliane House (1997) Translation Quality Assessment (TQA), the model focuses on the analysis between the relationship of the source text and the target text in order to identify mismatches, overtly or covertly erroneous errors and categorize the film into overt or covert translation approach. The findings revealed mismatches among Field and Tenor dimension, with the mismatches in Field mainly laid in the cultural reference and idiomatic expression, and in Tenor mainly laid in the style changes in Social Attitude from informal to formal, numerous overtly erroneous errors such as 1 breach of target language system error and 11 denotative meaning errors. The result of the research revealed that the translation quality of the Indonesian subtitle of the “Forrest Gump” film was faithful and fulfill the functional equivalent of its source text. The translator has seized almost every opportunity to enhance the language of the original.